Philadelphia [videorecording (DVD)] - Demme, Jonathan, 1944-2017; Demme, Jonathan, 1944-2017; Hanks, Tom; Washington, Denzel, 1954-; Steenburgen, Mary; Robards, Jason; Banderas, Antonio (Columbia TriStar Home Video, 2000)
A young Philadelphia lawyer stricken with AIDS seeks assistance from a homophobic personal injury attorney when a prestigious Philadelphia law firm fires him for incompetence.